Adaptation Processes of the Remaining Jejunum or Ileum after Extensive Intestinal Resection. Issue 4 (3rd April 2022) - Mussolino, Affonso Flávio Jorge; Tannuri, Ana Cristina Aoun; Gonçalves, Josiane de Oliveira; Serafini, Suellen; Tannuri, Uenis
Abstract: Purpose: To compare the adaptation processes of the remaining jejunum or ileum after extensive intestinal resection in a growing animal model. Materials and Methods: Forty 21-day old rats were divided into four groups: JG: remaining jejunum group – ileal enterectomy; IG: ileum remaining group – jejunum enterectomy; SHAM: sham-operated group – open-and-close laparotomy; and NO: non-operated animals. Results: After 3 weeks, JG and IG animals had decreased weights comparing to SHAM and NO animals (p = 0.017 and p = 0.005, respectively). The histomorphometric analysis showed that in JG animals the villi were higher than in SHAM, NO, and IG animals (p = 0.007, p = 0.008, and p = 0.01), the depth of crypts in JG and IG animals was greater than in NO and SHAM animals (p = 0.03, p = 0.002, and p = 0.003 respectively), and muscle layer thickness of the jejunum of JG animals had values greater than SHAM and NO animals (p = 0.01 and p = 0.02, respectively). The Ki-67 expression in the ileum was higher in comparison with the jejunum (p = 0.014). The pro-apoptotic gene (Bax) expression was decreased in JG animals compared to IG, SHAM, and NO animals (p = 0.013, p = 0.024, and p = 0.021). The anti-apoptotic gene (Bcl-XL) expression was decreased in JG animals in comparison to IG and NO animals (p = 0.002 and p = 0.046) although it was increased in the colon of IG animals in comparison to JG, SHAM, and NO animals (p = 0.002, p = 0.001, and p = 0.001, respectively). The Bax/Bcl-XL ratio was higher in JG than in IG animals (p = 0.011). Conclusion: Adaptive responses seemed to be more effective in the ileum than in the jejunum.